Incidence of Multi Drug Resistance and Diversity of TEM-1 Beta Lactamase in Gram Negative Bacteria Isolated from Clinical and Environmental Sample - Natarajan, K.; Subashkumar, R. (International Journal of Applied Sciences and Biotechnology, 2017)
Occurrence and incidence of drug resistant bacteria are becoming very high and common with overuse of antibiotics. This study focused on the isolation of drug resistant strains from the clinical and environmental sample that produce extended spectrum β-lactamase (ESBL) and identification of TEM-1 genes in the plasmid and genomic DNA. 45 Clinical samples from the hospital and 7 environmental samples from the polluted water sources were collected. Among the collected samples, E. coli showed a higher incidence (36.1 %) followed by Klebsiella sp., Staphylococcus sp., Streptococcus sp., Pseudomonas sp., Proteus sp., and Salmonella sp. Antibiotic susceptibility of the isolates were investigated against 25 commercially available antibiotics. All the isolated strains showed MAR index value of more than 0.2. Among the 36 isolates, 7 Gram negative isolates (19.4 %) showed positive results for ESBL production in Double disk synergy test. The plasmid and genomic DNA were isolated and analyzed using PCR with specific primers for the presence of the TEM-1 gene (716 bp). A selected PCR products of the TEM-1 gene was sequenced and analyzed using BLAST. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 302-308